2022
DOI: 10.1038/s41586-022-05055-8
|View full text |Cite
|
Sign up to set email alerts
|

Delayed use of bioenergy crops might threaten climate and food security

Abstract: The potential of mitigation actions to limit global warming within 2 °C1 might rely on the abundant supply of biomass for large-scale bioenergy with carbon capture and storage (BECCS) that is assumed to scale up significantly in the future 2-5 . However, the detrimental effects of climate change on crop yields may reduce the capacity of BECCS and threaten food security 6-8 , thus creating an unrecognized positive feedback loop on global warming. We quantified the strength of this feedback by implementing the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 86 publications
0
37
0
Order By: Relevance
“…The scenario is supposed to finally have a warming impact in comparison to the baseline scenario, whereas scenario exhibits a cooling effect, which is displayed in Figure S2. In addition to the enhancement of the earth’s radiation as the most apparent negative feedback, global warming would also lead to a slew of other direct and/or indirect feedback effects, which are not completely captured in this study. , The feedback process needs to be studied and evaluated later with comprehensive quantitative models available. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scenario is supposed to finally have a warming impact in comparison to the baseline scenario, whereas scenario exhibits a cooling effect, which is displayed in Figure S2. In addition to the enhancement of the earth’s radiation as the most apparent negative feedback, global warming would also lead to a slew of other direct and/or indirect feedback effects, which are not completely captured in this study. , The feedback process needs to be studied and evaluated later with comprehensive quantitative models available. , …”
Section: Resultsmentioning
confidence: 99%
“…The earth system model OSCAR v3.1 is used for the simulation of the climate system since the industrialization (1750∼). The model included all necessary components to simulate the past and future climate change, which has been widely used to study the contribution of human activity to climate, ,, and also applied to IPCC AR6 to study the response of future climate to multiple scenarios. All dynamic changes of different climate forcers are described by parametric equations with sources and sinks.…”
Section: Methodsmentioning
confidence: 99%
“…Xu (2018), Chang (2015) and Yu (2017) believe that the idea of “unity of nature and man” is the basis of contemporary ecological construction, and that the cultural heritage protection of traditional Chinese villages should apply the philosophy of “unity of nature and man” [ 6 , 7 , 8 ]. Singh et al (2020) and Chadalavada et al (2021) believe that environmental change will affect grain yield, and Xu (2022) strives to capture and store CO 2 on a large scale through a BECCS model [ 9 , 10 , 11 ]. Scholars have extracted ancient ecological protection theories from the landscape patterns of traditional villages, and some authors have used ancient trees in cultural heritage projects as an intermediary to explore theoretical methods of environmental protection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This includes corn straw, which is usually burned and thus causes environmental pollution and damages to the ecological balance of the soil. [ 4 , 5 , 6 ] The effective utilization of such raw materials has aroused great interests of researchers. Biorefineries utilize various components of biomass and its intermediates to maximize the value derived from the biomass feedstock, and carbohydrates (cellulose and hemicellulose) and lignin have been widely used in bioenergy and chemicals, such as, industries related to food production, pulp and paper industries, liquid and gas biofuels for road transport, aviation and shipping, all of which are remarkable examples of promising bio‐refining.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that about 900 million tons of agricultural and forestry wastes are produced in China per year. This includes corn straw, which is usually burned and thus causes environmental pollution and damages to the ecological balance of the soil [4–6] . The effective utilization of such raw materials has aroused great interests of researchers.…”
Section: Introductionmentioning
confidence: 99%